3D printing of metasurface-based dual-linear polarization converter. (10th December 2021) - Lee, Gyeongyeong; Noh, Yeong-Hoon; Lee, In-Gon; Hong, Ic-Pyo; Yook, Jong-Gwan; Kim, Jong-Yeong; Kim, Jihoon
Abstract: Three-dimensional printing using digital light processing (DLP) technology has been studied in various fields because of its ability to create complex shapes through a simple process. In this study, DLP 3D printing was employed in the implementation of the metasurface-based dual-linear polarization converter (DLPC). The unit cell of the metasurface-based DLPC for linear polarization conversion was designed consisting of the upper and lower dipole-pair antennas connected through vias and a shielding layer that electrically shields the antennas from each other, and its fabrication was based on the characterization results of the dielectric properties of the photocurable substrate materials and electrical properties of the conductive materials used for synthesizing the metasurface. The printability evaluation of dipole pairs, vias, and a shielding layer was carried out to implement the detailed structures of the DLPC in 3D printing. The electromagnetic wave transmission characteristics of the 3D-printed 8 × 8 array DLPC demonstrated an orthogonal polarization conversion, as predicted by the simulation results. This study confirmed that the DLP-based 3D printing technology can go beyond the existing functions of manufacturing objects and can be applied to the implementation of various electronics based on different meta-structures.